Do Land Market Restrictions Hinder Structural Change in a Rural Economy? Evidence from Sri Lanka - Emran, M. Shahe (World Bank E-Library Archive, 2015)
This paper analyzes the effects of land market restrictions on structural change from agriculture to non-farm in a rural economy. This paper develops a theoretical model that focuses on higher migration costs due to restrictions on alienability, and identifies the possibility of a reverse structural change where the share of nonagricultural employment declines. The reverse structural change can occur under plausible conditions: if demand for the non-agricultural good is income-inelastic (assuming the non-farm good is non-tradable), or non-agriculture is less labor intensive relative to agriculture (assuming the non-farm good is tradable). For identification, this paper exploits a natural experiment in Sri Lanka where historical malaria played a unique role in land policy. The empirical evidence indicates significant adverse effects of land restrictions on manufacturing and services employment, rural wages, and per capita household consumption. The evidence on the disaggregated occupational choices suggests that land restrictions increase wage employment in agriculture, but reduce it in manufacturing and services, with no perceptible effects on self-employment in non-agriculture. The results are consistent with the migration costs model, but contradict two widely discussed alternative mechanisms: collateral effect and property rights insecurity. This paper also provides direct evidence in favor of the migration costs mechanism